Case Report: Improvement from no light perception after radiotherapy and surgical debulking for orbital Rosai-Dorfman disease - Gary, Ashlyn A.; Dhodapkar, Rahul M.; Lim, Sean; Saber, Maria Sibug; Zhang-Nunes, Sandy (Frontiers in Ophthalmology, 2025)
Rosai-Dorfman disease (RDD) is a rare proliferative histiocytic disorder with ophthalmic manifestations occurring in 11% of cases. This report details the case of a 75-year-old woman presenting with orbital RDD characterized by right-sided proptosis and progressive vision loss, culminating in no light perception (NLP) for 8 months. Imaging studies revealed tumor involvement of the right ethmoid, maxillary, and sphenoid sinuses as well as the right orbit. Biopsy confirmed extranodal RDD. The patient underwent radiotherapy, which resulted in an improvement in the visual acuity to hand motion 3 months later. Subsequent orbital decompression surgery and tumor debulking were performed to address exophthalmos and worsening exposure keratopathy. Postoperatively, visual acuity improved to counting fingers at 6 in. in the first week and further to 20/800 seven months after surgery. Vision-threatening compressive optic neuropathy is a severe complication of orbital RDD; however, this case demonstrates its potential reversibility with a multidisciplinary therapeutic approach.